(untitled) (The Review of Diabetic Studies, 2024)
Chronic diseases, also referred to as noncommunicable diseases (NCDs), represent a major global health burden due to their long duration, progressive nature, and significant impact on physical, psychological, social well-being. As patients often live with these conditions for many years, improving health-related quality of life (HRQoL) has become a central goal of chronic disease management alongside clinical outcomes. Nursing plays a pivotal role in achieving this goal, as nurses are continuously involved in patient care, education, monitoring, and coordination across healthcare settings This paper examines the impact of nursing interventions on improving the quality of life of patients with chronic diseases. It highlights how nurse/led and nurse-coordinated care—including patient education, self-management support, medication management, symptom assessment, psychosocial support, and care coordination—contributes to enhanced patient activation, improved adherence to treatment plans, reduced symptom burden, and better functional outcomes. The study adopts a structured narrative review approach guided by a PICO-formulated research question to synthesize evidence from international literature, clinical frameworks, and validated quality-of-life measurement tools such as the SF-36, EQ-5D, and WHOQOL-BREF. Findings from previous studies and systematic reviews suggest that comprehensive and sustained nursing interventions are associated with significant improvements in HRQOL, particularly when integrated within multidisciplinary and chronic care models. The paper concludes that strengthening the role of nursing in chronic disease management is essential for improving patient-centered outcomes and overall quality of life, and it underscores the need for health systems to invest in advanced nursing roles, standardized outcome evaluation, and supportive policies to optimize long-term care for individuals living with chronic diseases.